Disruption of genes encoding subunits of yeast vacuolar H(+)-ATPase causes conditional lethality. - Nelson, H (1990)
The main function of vacuolar H(+)-ATPases in eukaryotic cells is to generate proton and electrochemical gradients across the membranes of the vacuolar system. The enzyme is composed of a catalytic sector with five subunits (A-E) and a membrane sector containing at least two subunits (a and c). We disrupted two genes of this enzyme, in yeast cells, one encoding a subunit of the membrane sector (subunit c) and another encoding a subunit of the catalytic sector (subunit B). The resulting mutants did not grow in medium with a pH value higher than 6.5 and grew well only within a narrow pH range around 5.5. Transformation of the mutants with plasmids containing the corresponding genes repaired the mutations. Thus failure to lower the pH in the vacuolar system of yeast, and probably other eukaryotic cells, is lethal and the mutants may survive only if a low external pH allows for this acidification by fluid-phase endocytosis.